Reading Comprehension (Journal of Parents and Teachers, 2013)
Over the last years, the concept of reading has been focusing on the processes of reading comprehension: it is important to know the meaning of the text, extract it and then, being conscious of it in our minds. This article offers a complete definition of this concept and points out the problems that are often related to it.
Keywords: Text comprehension; Reading difficulty; Reading; Education.